The Use of Bee Wax, Chitosan and BAP to Prolong Shelflife of Mangosteen (Garcinia mangostana L.) Fruit - Darda Efendi; Heliyana Hermawati (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2010)
ABSTRACTThe objective of this research was to determine the effect of coating materials and BAP concentration on inhibition of ripening process of mangosteen. The experiment used factorial completely randomized design with two factors, and three replication s. Coating materials as the first factor consisted of control (without coating) , bee wax 6%, and chitosan 2%. The second factor was concentration of Benzil Amino Purine (BAP), with 0, 5, 10, 15, and 20 ppm. Non destructive observations were weight loss, diameter decrease, peel and calyx color development. While, destructive observations were fruit hardness, total soluble solid (TSS), total titratable acidity (TTA) and opened ability. The result showed that bee wax was effective to inhibit weight loss. Interaction of bee wax and BAP 20 ppm inhibited peel and calyx color changes during storage.Key word: coating material, cytokinin, benzil amino purine, calyx, storage